2015
DOI: 10.1145/2766897
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous codes for energy-efficient illumination and imaging

Abstract: Figure 1: Imagine trying to acquire live video (30fps) of structured-light patterns as they are being projected onto a compact fluorescent bulb that has already been turned on (rated 1600 Lumens), or onto a face in bright sunlight (80 kLux)-with a 5-Lumen projector. One of our two prototypes, shown in (a), achieves this with an off-the-shelf laser projector and a CMOS camera with an ordinary lens. We then used it to capture the video frames in (b) and (c). We also show how to use our prototype to generate a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…In the field of structured-light reconstruction, several studies have suggested adaptive scanners (see for example [8,19,20,37]), and energy-efficient designs [24]. However, unlike previous attempts that observed specific image features and addressed a specific pattern decoding technique, we show how given a generative model for the sensing process we can obtain an adaptive scanner for various tasks, forming a decision-theoretic purposive [22] 3D scanner.…”
Section: Introductionmentioning
confidence: 80%
“…In the field of structured-light reconstruction, several studies have suggested adaptive scanners (see for example [8,19,20,37]), and energy-efficient designs [24]. However, unlike previous attempts that observed specific image features and addressed a specific pattern decoding technique, we show how given a generative model for the sensing process we can obtain an adaptive scanner for various tasks, forming a decision-theoretic purposive [22] 3D scanner.…”
Section: Introductionmentioning
confidence: 80%
“…We would like to explore more sophisticated temporal coding strategies that may be able to separate direct and global illumination based on their temporal characteristics rather than their polarisation properties. We would also like to explore spatio-temporal coding strategies that would allow the light sources to be used as temporally-coded projectors rather than isotropic emitters [O'Toole et al 2015]. Finally, we would like to extend the application to mitigating multi-path interference for time-of-flight cameras and other tasks that may benefit from gradient cameras, such as Visual SLAM [Kim et al 2016] and 3D scanning [Matsuda et al 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Although photometric stereo can recover surface normals, they cannot recover absolute 3D distances; thus, their applicability is limited. The structured light technique has been used for practical applications [16,22,12]. Two primary approaches to encode positional information into patterns are temporal and spatial encoding.…”
Section: Related Workmentioning
confidence: 99%